Excellent performance of W–Y2O3 composite via powder process improvement and Y2O3 refinement - Yao, Gang; Liu, Xuepeng; Zhao, Zhihao; Luo, Laima; Cheng, Jigui; Zan, Xiang; Wang, Zumin; Xu, Qiu; Wu, Yucheng (Materials & design, 2021)
[Display omitted] •An improved wet chemical method where the TEA surfactant addition and an appropriate calcination process are employed is developed to fabricate ultrafine W-Y2O3 composite powders.•The W-Y2O3 composites possess superior mechanical properties compared with the pure tungsten counterparts.•Molecular dynamics simulation analysis reveals the strengthening microscopic mechanism of second phase particles on the mechanical performances of W-Y2O3 composites.•The addition of Y2O3 second phase particles is capable of improving the helium ion irradiation resistance of tungsten-based composites. In this article, Y2O3-reinforced tungsten composites are fabricated by using an improved wet chemical method combined with the spark plasma sintering (SPS). Triethanolamine (TEA) surfactant addition and an appropriate calcination process are innovatively introduced into this wet chemical method. The results show that ultrafine composite powders with nano-sized Y2O3 dispersions in the tungsten matrix can be obtained through the improved wet chemical method. Using the SPS, the average sizes of Y2O3 particles within tungsten grains and at grain boundaries are identified to be 13.5 and 50 nm, respectively. It is found that the phase interface between W and Y2O3 is a typical semicoherent interface. We observe that the W-Y2O3 composites possess superior mechanical properties compared with the pure tungsten counterparts. The results inferred from atomistic simulations reveal that the added Y2O3 particles can effectively pin the dislocation and impede the dislocation movement, thus enhancing the mechanical performances of W-Y2O3 composites. In addition, the addition of Y2O3 particles is also able to improve the helium ion irradiation resistance of tungsten-based composites. This study is expected to provide a certain reference for the manufacture of large-sized tungsten-based materials.